Buffalo Immune Competence Under Infectious and Non-Infectious Stressors - Maria Giovanna Ciliberti; Antonella Santillo; Mariangela Caroprese; Marzia Albenzio (Animals)
Immune competence is a critical aspect of protecting animals from the negative consequences of disease. The activation of the immune response from inflammation is part of adaptive homeostasis that serves to eliminate danger, induce tissue repair, and restore tissue homeostasis. Therefore, the main goal for the organism is to control both the induction and suppression of inflammation and resist the onset of disease. In this condition, modulators of inflammatory responses are produced, including small proteins called cytokines, which exert a pro- or anti-inflammatory action in a context-dependent manner. Indeed, the cytokine profile could be considered a useful biomarker to determine the pathophysiology of certain diseases, such as mastitis, endometritis, change-induced heat stress, and zoonoses. Recently, buffalo breeding has attracted the interest of the research communities due to their high resilience; however, little is known about the immune mechanism activated under specific stressors. This review describes the complex immune competence of the buffalo in the presence of the most common infectious and non-infectious stressors. In addition, a brief description of methods for early diagnosis of disease using cytokine quantification will be introduced.